Geometrically Enabled Soft Electroactuators via Laser Cutting. Issue 11 (19th November 2019) - Yan, Bingxi; Ma, Chunping; Zhao, Yinghao; Hu, Nan; Guo, Liang
Abstract : "Patterning the Motion" is achieved by lasing rationally selected 2D architectures in an electroactive polypyrrole composite film as described by Nan Hu, Liang Guo and co‐workers, article number 1900664 . Depending on the patterns chosen, the film's initial bending strain rapidly transforms into gripping, flapping, pulling or squeezing, with unprecedented consistency in structuring and performance. A broad path to engineerable soft electroactuators featuring geometrically‐augmented robotic capabilities is now open.